1984
DOI: 10.2307/1510316
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Illustrations on Learning Disabled Students' Reading Performance

Abstract: An alternating-treatments design was used to investigate the relative effects of illustrations on the oral reading in context and comprehension accuracy of five elementary-school learning disabled students. Social comparison data were used to verify oral reading deficiencies. Results showed no apparent relationship between the presence or absence of illustrations and changes in oral reading rates or response accuracy of comprehension questions. Results are discussed in relation to the purported benefits of ill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Still others may not look at them at all. Surely the usefulness of graphic aids varies from reader to reader, but previous research suggests that they may be less useful for poor readers than for other readers (Braun, 1969;Harber, 1980Harber, , 1983Koenke & Otto, 1969;Rose & Furr, 1984;Rose & Robinson, 1984;Willows, 1978). The research reported here investigated one possibility for improving poor readers' use of graphic aids in text, namely supplying them with explicit instructions in the text to attend to the graphic aids available.…”
mentioning
confidence: 99%
“…Still others may not look at them at all. Surely the usefulness of graphic aids varies from reader to reader, but previous research suggests that they may be less useful for poor readers than for other readers (Braun, 1969;Harber, 1980Harber, , 1983Koenke & Otto, 1969;Rose & Furr, 1984;Rose & Robinson, 1984;Willows, 1978). The research reported here investigated one possibility for improving poor readers' use of graphic aids in text, namely supplying them with explicit instructions in the text to attend to the graphic aids available.…”
mentioning
confidence: 99%
“…Graphics have no effect on comprehension of written text A number of studies (e.g., Brookshire, Scharff, & Moses, 2002;Miller, 1938;Rose & Robinson, 1984) conducted with children found that the presence of graphics had no effect on the participants' comprehension. For example, Brookshire et al (2002) randomly assigned first-and third-grade students to one of three conditions for reading a narrative text designed specifically for the experiment: text-only, text plus illustrations, and illustrations-only (for which the students were told the names of the characters and instructed to make up a story).…”
Section: Comprehension Of Graphicsmentioning
confidence: 99%
“…Although illustrations can make materials more attractive, and thus more interesting, some experts have argued that illustrations can have a detrimental effect on LD students' reading, particularly if students have poorly developed basic reading skills or if the pictures present ambiguous or inaccurate information (cf. Harber, 1983;Rose & Robinson, 1984;Rose, 1986). The most important questions regarding illustrations, however, may center on the quality of the picture.…”
Section: Exceptional Childrenmentioning
confidence: 99%